A conceptual model of online hotel booking: the role of online review and online trust towards online booking intention / Fadhlina Mahat... [ et al.] - Mahat, Fadhlina; Abdullah, Dahlan; Bahari, Khairil Anuar; Che Azmi, Nuruddin; Mohd Kamal, Saiful Bahri; Zainol, Noorliza (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
A growing reliance on the Internet as an information source when making choices about hotel booking raises the need for more research into this issue. Within online hotel booking context, this study aims to investigate the influence of online review and online trust towards online booking intention. Furthermore, the mediating role of online trust will also have been examined. Based on review of past literature, six dimensions of online review construct are proposed namely, usefulness, reviewer expertise, timeliness, volume, valence and comprehension as predictors. The proposed model is supported by Stimulus-Organism-Response (S-O-R) model developed by Mehrabian and Rusell (1974). In the present study, online review is conceptualized as a second order construct. It is predicted that online review has positive effect on both online trust and online booking intention. Besides, online trust is predicted to has a positive effect on online booking intention. Finally, it is expected that the online trust mediates the relationship between online review and online booking intention. This study contributes to the existing body of knowledge by examining the role of online trust as mediator.